Perbandingan Debit Limpasan Metode Rasional dan Pemodelan SWMM Jaringan Drainase Jalan Parangtritis KM 3,5-4,5: Comparison of Runoff Discharge Using Rational Method and SWMM Modeling for The Drainage Network of Parangtritis Road, KM 3.5-4.5 - Widyasari, Titiek; Meigawati, Inanda Andita (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2024)
This research aims to compare runoff discharge using the rational method and the Storm Water Management Model (SWMM) modeling in a case study of drainage on Parangtritis Road KM 3.5-4.5, which consists of 11 sub catchments. The total runoff discharge for the rational method with a return period of 2 years is 0.90 m³/s, for 5 years is 1.22 m³/s, and for 10 years is 1.60 m³/s, and from the SWMM modeling, a return period of 2 years is 1.28 m³/s, for 5 years is 1.79 m³/s, and for 10 years is 2.44 m³/s. The runoff coefficient from the SWMM modeling is greater than the runoff coefficient from the rational method, and the runoff discharge from the SWMM modeling is higher than that from the rational method. This is caused by the runoff coefficient of the rational method, which assumes a waterproof layer in the form of closed multi-unit housing and the percentage of imperviousness in each watershed area. After correction, the results of runoff calculations using the rational method will be the same as the runoff calculations from SWMM modeling if the runoff coefficient of the rational method is equal to that of the SWMM modeling.